New directions of trade for the agri-food industry: A disaggregated approach for different income countries, 1963 - 2000 - Raúl Serrano; Vicente Pinilla Navarro (Latin American Economic Review, 2014)
The principal objective of the present study is to explain the changes in the direction of agri-food trade flows during the second half of the twentieth century. Since the end of the Second World War, trade has tended to be concentrated among developed countries, breaking the pattern of complementarity among industrialized countries and developing countries from the first wave of globalization. Elsewhere, agricultural exports from developing countries to countries of similar income have significantly increased since the 1990s. To compare and explain the evolution of different trade directions, the present article estimates the gravity equation for the bilateral volume of agri-food trade, analyzed separately in four categories of trade flows based on the development level of countries. Specifically, we have used the UN-COMTRADE database to construct a data panel for bilateral trade among 30 reporting countries and 39 partner countries with a significant presence in international markets for the period 1963 - 2000. The following conclusions can be extracted from the present study. Firstly, while other types of trade, such as manufactures, enjoyed greater multilateral liberalization of their markets, strong market intervention caused them to base their growth on the proliferation and success of regional trade agreements in the North. As a result, agri-food trade concentrated progressively on developed economies. Secondly, the latest liberalization of some preferential trade agreements gave rise to new increases in agricultural trade, this time in South-South flows. Finally, the negative sign of income demand elasticity for imports of agricultural products from Southern countries demonstrates that the latter behaved like inferior goods and also explains why the export growth of such countries suffered a brake on such expansion.
Keywords: F14; M16; N50; N70; Q17; 330; Agri-food trade; Gravity equation; Regional trade agreements; Agri-food industry